FKBP38 protects Bcl-2 from caspase-dependent degradation - Choi, Bo-Hwa (2012)
The cellular processes that regulate Bcl-2 at the posttranslational levels are as important as those that regulate bcl-2 synthesis. Previously we demonstrated that the suppression of FK506-binding protein 38 (FKBP38) contributes to the instability of Bcl-2 or leaves Bcl-2 unprotected from degradation in an unknown mechanism. Here, we studied the underlying molecular mechanism mediating this process. We first showed that Bcl-2 binding-defective mutants of FKBP38 fail to accumulate Bcl-2 protein. We demonstrated that the FKBP38-mediated Bcl-2 stability is specific as the levels of other anti-apoptotic proteins such as Bcl-XL and Mcl-1 remained unaffected. FKBP38 enhanced the Bcl-2 stability under the blockade of de novo protein synthesis, indicating it is posttranslational. We showed that the overexpression of FKBP38 attenuates reduction rate of Bcl-2, thus resulting in an increment of the intracellular Bcl-2 level, contributing to the resistance of apoptotic cell death induced by the treatment of kinetin riboside, an anticancer drug. Caspase inhibitors markedly induced the accumulation of Bcl-2. In caspase-3-activated cells, the knockdown of endogenous FKBP38 by small interfering RNA resulted in Bcl-2 down-regulation as well, which was significantly recovered by the treatment with caspase inhibitors or overexpression of FKBP38. Finally we presented that the Bcl-2 cleavage by caspase-3 is blocked when Bcl-2 binds to FKBP38 through the flexible loop. Taken together, these results suggest that FKBP38 is a key player in regulating the function of Bcl-2 by antagonizing caspase-dependent degradation through the direct interaction with the flexible loop domain of Bcl-2, which contains the caspase cleavage site.